HER2 Positivity in Histological Subtypes of Salivary Gland Carcinoma: A Systematic Review and Meta-Analysis - Egebjerg, Kristian; Harwood, Cecilie Dupont; Woller, Nina Claire; Kristensen, Claus Andrup; Mau-Sørensen, Morten (Frontiers in Oncology, 2021)
Background: HER2 aberrations in salivary gland carcinomas (SGC) as well as benefit of HER2 directed therapy have been reported in small studies. However, reliable estimates of the prevalence of HER2 positivity in SGC and its various histological subtypes are lacking. Objective: To assess the prevalence of HER2 positivity in histological subtypes of salivary gland carcinomas (SGC). Methods: Studies were identified by a systematic review of the literature. Data on in situ hybridization (ISH) and immunohistochemistry (IHC) were extracted to derive pooled prevalence estimates calculated by a random effects model. Characteristics of the studies were extracted for subgroup analysis. Results: Fifty studies including 3372 patients were identified, providing data on sixteen histological subtypes. Based on the meta-analysis, the estimated prevalence of HER2 positivity were 43% (95% CI: 36% – 51%) in salivary duct carcinoma (SDC), 39% (95% CI: 32% – 45%) in carcinoma ex pleomorphic adenoma (CEP), 17% (95% CI: 7.5% – 33%) in squamous cell carcinoma (SCC), 13% (95% CI: 7.6% – 21%) in adenocarcinoma NOS (ADC), 6.7% (95% CI: 0.17%-32%) in poorly differentiated carcinoma, 5.5% (95% CI: 2.9% – 9.6%) in mucoepidermoid carcinoma, 4.3% (95% CI: 1.4% – 13%) in myoepithelial carcinoma, 1.8% (95% CI: 0.04%-9.6%) in epithelial-myoepithelial carcinoma, 0.45% (95% CI: 0.0097% – 18%) in acinic cell carcinoma and 0.15% (0.037% – 5.4%) in adenoid cystic carcinoma. Estimates for five additional subtypes were assessed. Conclusion: Prevalence of HER 2 positivity in SGC varies greatly based on histological subtype, with SDC, CEP, SCC, and ADC displaying the highest rates.